(untitled) (Texas Journal of Medical Science, 2026)
This article analyzes modern problems in the practice of echocardiography (EchoCG), which is the primary method in the non-invasive diagnosis of cardiovascular diseases. The dependence of image quality on the patient’s constitution, subjectivity in measurements (human factor), as well as issues of standardization of new technologies such as 3D EchoCG and Speckle Tracking are highlighted. The role and prospects of artificial intelligence (AI) technologies in overcoming these problems are evaluated.